2018
DOI: 10.2903/j.efsa.2018.5337
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of vitamin B2 (riboflavin) produced by Ashbya gossypii DSM 23096 for all animal species based on a dossier submitted by BASF SE

Abstract: The European Commission asked EFSA for an opinion on the safety for the target animals, consumer, user and the environment and on the efficacy of a riboflavin‐based additive (minimum 80%) produced by a genetically modified strain of Ashbya gossypii (■■■■■). It is intended to be used in feed for all animal species and categories. The additive under assessment does not give rise to safety concerns on the genetic modification of the production strain. The additive contains 80% of riboflavin (vitamin B2) and 20% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This conclusion also applies to riboflavin 5 0 -phosphate. In its previous opinions on vitamin B 2 , the FEEDAP Panel supported the conclusions of the ANS Panel concerning the vitamin 'per se' (EFSA FEEDAP Panel, 2014, 2018b.…”
Section: Toxicological Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…This conclusion also applies to riboflavin 5 0 -phosphate. In its previous opinions on vitamin B 2 , the FEEDAP Panel supported the conclusions of the ANS Panel concerning the vitamin 'per se' (EFSA FEEDAP Panel, 2014, 2018b.…”
Section: Toxicological Studiesmentioning
confidence: 88%
“…The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) issued two opinions on the safety and efficacy of vitamin B 2 (80%) as riboflavin produced by Bacillus subtilis KCCM-10445 for all animal species (EFSA FEEDAP Panel, 2014, 2018a, an opinion on the safety and efficacy of vitamin B 2 as riboflavin and riboflavin-5 0 -phosphate ester monosodium salt, produced by either Bacillus subtilis DSM 17339 or Bacillus subtilis DSM 23984 (EFSA FEEDAP Panel, 2016), and another opinion on the safety and efficacy of vitamin B 2 (riboflavin) produced by Ashbya gossypii (EFSA FEEDAP Panel, 2018b).…”
Section: Additional Informationmentioning
confidence: 99%
“…In previous assessments, the FEEDAP Panel concluded that riboflavin is safe for the target animals with a wide margin of safety, of about 20-60 compared to the supplementation levels in commercial feed (EFSA FEEDAP Panel, 2014, 2016, 2018b. Therefore, the additive under assessment would not represent a concern for the target species considering the levels of riboflavin proposed to be added to the feeds.…”
Section: Safety For the Target Speciesmentioning
confidence: 99%
“…In previous assessments, the FEEDAP Panel concluded that the supplementation of feed with riboflavin could not be of concern for the consumers (EFSA FEEDAP Panel, 2014, 2016, 2018b. However, apart from riboflavin, the toxicological profile of the other components of the additive, which is a fermentation product, has not been established, and therefore, uncertainties remain as regards to the safety for the consumers of food products obtained from animals receiving the additive under assessment.…”
Section: Safety For the Consumermentioning
confidence: 99%
“…Ashbya gossypii is an industrial filamentous fungus that is currently used for the microbial production of vitamin B 2 (Revuelta et al ., ). Indeed, the worldwide riboflavin market mostly relies on A. gossypii bioprocessing, which provides the vitamin as a safe additive for human foodstuffs and animal feeding (Schwechheimer et al ., ; Rychen et al ., ). In addition, A. gossypii has been also shown as an appropriate biotechnological chassis for other applications such as the production of folic acid (Serrano‐Amatriain et al ., ), microbial oils (Ledesma‐Amaro et al ., , ; Lozano‐Martínez et al ., ; Díaz‐Fernández et al ., ), nucleosides (Ledesma‐Amaro et al ., ) and recombinant proteins (Aguiar et al ., , ).…”
Section: Introductionmentioning
confidence: 99%